The design of the measurement circuit using ultrasonic sound waves for fuel level of automobile tanks and the detection of bad sectors of tank by neural networks - Dalci, KB; Gulez, K; Mumcu, TV (SOC INSTRUMENT CONTROL ENGINEERS JAPAN, 2004)
In recent years, control systems have assumed an increasingly important in the development and advancement of modem civilization and technology. Practically, every aspect of day-to-day activities is affected by some type of control system. Control systems are found in abundance in all sectors of industry such as quality control of manufactured products, automatic assembly line, machine-tool control, space technology and weapon systems, computer control, transportation systems, power systems, robotics, automobile sector as well. These kinds of technologic developments in automobile sector are especially on electronic gear, balance, anti-slip, security systems. The other important application of them is the measurement system which has the same age with automobile history for fuel level of automobile tanks. There is an obligation to use the float systems for automobile companies because of bad operating conditions in the tank such as high temperature and humidity.Buts the float system works as if it is a warning lamp more than a measurement component since it has a connection with adjustable resistance which has a nonlinear structure and low solution one. In this application, it is used ultrasonic sound waves which are not affected from bad operating conditions to be able to give the quantity of fuel level as litre in the tank to the driver and make the measurement system more sensitive. Also, The volume of the tank is modeled. The model according to dimensions which the tank is produced is stored to the training phase of the neural network.
Keywords: ultrasonic sound waves; measurement system for fuel level; automobile tanks; bad sector detection; neural networks; Automation & Control Systems; Computer Science; Robotics